Dynamics and Outcome of Macrophage Interaction Between Salmonella Gallinarum, Salmonella Typhimurium, and Salmonella Dublin and Macrophages From Chicken and Cattle - Huang, Kaisong; Fresno, Ana Herrero; Skov, Søren; Olsen, John Elmerdahl (Frontiers in Cellular and Infection Microbiology, 2020)
Salmonella Gallinarum only infects avian species, where it causes a severe systemic infection in birds of all age. It is generally accepted that interaction with phagocytic cells plays an important role in the development of systemic, host-specific Salmonella infections. The current study detailed the interaction of S. Gallinarum with macrophages derived from chicken (HD11) and cattle (Bomac) compared to interaction of the broad host range serovar, S. Typhimurium and the cattle adapted serovar S. Dublin. Results showed a weaker invading ability of S. Gallinarum in both kinds of macrophages, regardless of whether the bacteria were opsonized or not before infections. However, oposonization of S. Gallinarum by chicken serum increased its intracellular survival rate in chicken macrophages. No significant induction of nitrogen oxide was observed in the infected HD11 cells within the first 6 hours, and levels of ROS species were similar among the three serovars. S. Gallinarum infection was associated with low cell deaths in both chicken and cattle macrophages, while S. Dublin only induced a comparable high level of cell death in chicken macrophages, but not in macrophages of its preferred host species (BoMac) compared to host-generalist S. Typhimurium. S. Gallinarum infected HD11 macrophages exhibited low induction of pro-inflammation genes (IL1β, CXCLi1 and CXCLi2) compared to the two other serovars, and contrary to the other serovars, it did not induce significant down-regulations of TLR2, TLR4 and TLR5. In in vivo infection of one-week old chicken, a significant up-regulation of the TLR4 and TLR5 genes in the spleen was observed in S. Gallinarum infected chickens, but not in S. Typhimurium infected chicken at 5 days post-infections. Taken together, results show that S. Gallinarum infection of macrophages was characterized by low uptake and low cytotoxicity, possibly allowing long-term persistence in the intracellular environment, and it caused a low induction of pro-inflammatory responses.